You first : inspire your team to grow up, get along, and get stuff done - Davey, Liane, 1972- (John Wiley & Sons, Inc., 2013)
Five common problems your team is susceptible to--and the one thing you can do to fix all of them You First will help you figure out how to make your team happier, healthier, and more productive.